2020
DOI: 10.1002/aelm.201901304
|View full text |Cite
|
Sign up to set email alerts
|

Atomically Controlled Tunable Doping in High‐Performance WSe2 Devices

Abstract: Two-dimensional transitional metal dichalcogenide (TMD) field-effect transistors (FETs) are promising candidates for future electronic applications, owing to their excellent transport properties and potential for ultimate device scaling. However, it is widely acknowledged that substantial contact resistance associated with the contact-TMD interface has impeded device performance to a large extent. It has been discovered that O2 plasma treatment can convert WSe2 into WO3-x and substantially improve contact resi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 46 publications
4
52
3
Order By: Relevance
“…This implies in particular that monolayer TMD devices are expected to receive strong contact gating and good injection into the channel, but the device ON-state may suffer from too large R C -values associated with a large SBH at the contact interface as mentioned above [18], [19]. Therefore, further studies on the topics of reliable doping schemes [25]- [29], phase change contacts [30], [31], and contact Fermi-level depinning [32]- [34] are urgently required to facilitate the integration of 2-D TMD-based CMOS for a beyond-Si era.…”
Section: -Dmentioning
confidence: 99%
“…This implies in particular that monolayer TMD devices are expected to receive strong contact gating and good injection into the channel, but the device ON-state may suffer from too large R C -values associated with a large SBH at the contact interface as mentioned above [18], [19]. Therefore, further studies on the topics of reliable doping schemes [25]- [29], phase change contacts [30], [31], and contact Fermi-level depinning [32]- [34] are urgently required to facilitate the integration of 2-D TMD-based CMOS for a beyond-Si era.…”
Section: -Dmentioning
confidence: 99%
“…Recently, Pang et al reported that surface dopants diffuse to the transfer length of devices even with the hard mask used for the electrical contact region. [41] Besides, they also reported the Fermi-level depinning by p-type doping. [42] Moreover, PVA as a dielectric layer provides a screening effect to long-range charge scattering, alleviating FLP.…”
Section: Dmentioning
confidence: 99%
“…At the same time, the intentional placement of charges at the interface could be used to shift the band edges away from the oxide defect bands using, for example, surface charge transfer doping 43 . However, fixed charges at the interfaces would also degrade the mobility in the semiconducting 2D channel 25 .…”
Section: Fermi-level Tuning For Increasing Stability Of 2d Fetsmentioning
confidence: 99%